Spectrophotometric Method for Determination Folic Acid via Diazotization and Coupling with 4-Aminoantipyrine - Resala A. Saleh (Journal of Global Pharma Technology, 2020)
Uncommon coupling reagent is used for the simple and sensitive spectrophotometric determination of folic acid in pure form and in its pharmaceutical preparations. The method is based on the diazotization of the p-aminobenzoyl glutamic acid formed after reductive cleavage of folic acid, followed by coupling 4-amino antipyrine to give an orange product with λmax of 469nm. The results follow ‘Beer’s law in the concentration range of 2-100 µg.mL-1 with molar absorptive of 3266.36 L.mol-1.cm-1. The limit of detection was found to be 0.1482 µg.mL-1 and the Sandell’s sensitivity value was 0.1351 µg.cm-2. Common excipients used as additives in pharmaceutical preparations do not interfere in the proposed methods. The proposed method was successfully applied to the determination of folic acid in pharmaceutical preparations.Keywords: Folic Acid; Spectrophotometry; 4-Aminoantipyrine